Why Do German Men Marry Women from Less Developed Countries? An Analysis of Transnational Partner Search Based on the German Socio-Economic Panel - David Glowsky (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper examines why German men marry women from countries which are less economically developed. Two hypotheses deduced from exchange theory and the economic theory of the family are tested: 1. Low physical and social attractiveness as well as reduced opportunities to meet German partners lead to marriage with a woman from a poorer country. 2. Because of the economic gap between their countries of origin, German men can marry comparatively more attractive women on the international marriage market than they could hope to attract within Germany. The analysis uses data from the German Socio-Economic Panel (GSOEP, 1984-2005). The results show that men with wives from poorer countries do not differ from men with German wives with regard to their attractiveness and social contacts. A better explanation for these marriages lies in the age-related "marriage squeeze" encountered by German men older than 30 years. Only on account of their age do these men struggle to find a spouse on the German marriage market, which in turn increases the likelihood of them seeking marriage with women from poorer countries. Furthermore, the results do offer strong evidence that the economic gap between their countries of origin does allow German men to marry more attractive women when they opt for partners from poorer countries.
Keywords: 330; Marriage market; marriage migration; marriage squeeze; age difference; social status; attractiveness